sebagai, pada Pemberdayaan Kelompok Pengolah Ikan Asap Prigi, Trenggalek Melalui Pelatihan Aplikasi Kitosan sebagai Biopreservasi pada Ikan Asap - Suseno, Sugeng Heri; Albarokah, Nurdiansyah; Hartono, Arief; Kustiariyah, Kustiariyah; Miftahudin, Miftahudin; Arafah, Purnama; Setiawan, Jeffry; Kamini, Kamini; Salimah, Hafshah Aqidatun (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
A training program on the application of chitosan as a natural coating agent for smoked fish products was conducted for the Smoked Fish Processing Group at the Mushola Bukit Salam Rest Area, Prigi Village, Trenggalek Regency. The objective of this training was to enhance participants' knowledge and skills in utilizing chitosan as a natural preservative to extend shelf life and improve the quality of smoked fish. The training activities included interactive lectures, practical demonstrations on the preparation of chitosan solution, and evaluations comparing the shelf life of treated and untreated smoked fish products. Observational results indicated that smoked fish coated with chitosan exhibited a longer shelf life and greater resistance to fungal growth and insect contamination compared to uncoated samples. Additionally, questionnaire-based evaluations revealed a significant increase in participants’ understanding of the benefits and applications of chitosan. The training received highly positive feedback, with participants expressing interest in the continuation of similar programs. These findings suggest that chitosan training positively contributes to the capacity of local fish processors to produce safer, more hygienic, and market-competitive smoked fish products.